The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1152/ajpregu.1996.270.2.r427
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration natriuresis in male rats is mediated by oxytocin

Abstract: In a previous study in rats we demonstrated the existence of osmoregulatory natriuretic mechanisms distinct from the natriuretic mechanisms that are dependent on volume stimulation. At the same time, we found that oxytocin (OT) receptors were important mediators of natriuresis induced by hypernatremia but not of that induced by isotonic volume expansion. In the present study, the role of OT in dehydration natriuresis was examined in conscious rats. Dehydration for 24 h caused hypernatremia (from 142.1 +/- 0.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 0 publications
2
48
1
1
Order By: Relevance
“…19 WD caused a significant reduction in plasma volume and a rise in hematocrit, which is concordant with previous results. 20 We had expected that because pregnant rats were actively retaining water, WD could cause a greater reduction on plasma volume in this group. However, the percentage decrease in plasma volume was almost identical to that observed in nonpregnant rats.…”
Section: Salas Et Al Water Deprivation In Pregnant Rats 337mentioning
confidence: 99%
“…19 WD caused a significant reduction in plasma volume and a rise in hematocrit, which is concordant with previous results. 20 We had expected that because pregnant rats were actively retaining water, WD could cause a greater reduction on plasma volume in this group. However, the percentage decrease in plasma volume was almost identical to that observed in nonpregnant rats.…”
Section: Salas Et Al Water Deprivation In Pregnant Rats 337mentioning
confidence: 99%
“…Oxytocin release is known to be stimulated by dehydration (Windle et al 1993, Huang et al 1996, hypertonic saline loading (Balment et al 1980, Huang et al 1995 and partial nephrectomy (Huang et al 1994), i.e. situations which all result in enhanced sodium excretion (in the latter case by the surviving nephrons).…”
Section: Introductionmentioning
confidence: 99%
“…However, only fragmentary information is available concerning the effects of oxytocin antagonists in the absence of infused hormone. Huang et al (1996) administered an antagonist by osmotic minipump to conscious rats and observed a small reduction in sodium excretion, but the significance of this was obscured by a comparable reduction in sodium intake (as a result of the minipump implantation procedure). Similarly, a study in anaesthetized animals showed a small (non-significant) reduction in sodium excretion, but the antagonist was administered for only 60 min before a confounding manoeuvre (unilateral nephrectomy) was superimposed (Huang et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The HNS also produces the closely related hormone oxytocin (OXT), which acts to promote kidney natriuresis (Huang et al, 1996). Single-cell RT-PCR enables AVP and OXT transcripts to be detected in the same MCN (Glasgow et al, 1999), but the expression levels of each neuropeptide RNA differ by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%